STRATEGI MANAJEMEN PEMBIAYAAN PENDIDIKAN PADA SEKOLAH DASAR - Sonny Muhammad Ikhsan Mangkuwi; Ahmad Tarmizi; Eva Kristina; Heri Kurnila (CV. Adiba Aisha Amira, 2025)
This study aims to examine the strategies of educational financing management in primary schools. The primary focus of this study is on how educational institutions manage, distribute, utilise, and evaluate financial resources to help students achieve their learning objectives. This study employs a qualitative descriptive methodology, collecting data through document analysis, observation, and interviews. According to the study's findings, schools employ a number of tactics, including participatory budgeting involving stakeholders, prioritising expenditures based on educational requirements, and open and accountable financial reporting. These tactics are considered successful in improving the accountability and efficiency of education fund management. Schools still face problems such as a lack of financial resources, dependence on government support, and delays in budget delivery. These results highlight the importance of good financial management plans to maintain the quality and sustainability of basic education services. Therefore, to maximise the use of education funds, it is recommended to seek alternative financial sources and enhance financial management competencies at the school level.